Crystal structures of diaquadi-μ-hydroxido-tris[trimethyltin(IV)] diformatotrimethylstannate(IV) and di-μ-hydroxido-tris[trimethyltin(IV)] chloride monohydrate - Otte, Felix; Koller, Stephan G.; Golz, Christopher; Strohmann, Carsten (Technische Universität Dortmund, 2016)
The title compounds, [Sn3(CH3)9(OH)2(H2O)2][Sn(CH3)3(CHO2)2] (1) and [Sn3(CH3)9(OH)2]Cl·H2O (2), are partially condensed products of hydrolysed trimethyltin chloride. In the structures of 1 and 2, short cationic tristannatoxanes (C9H29O2Sn3) are bridged by a diformatotrimethyltin anion or a chloride anion, respectively. Hydrogen bridges are present and supposedly stabilize these structures against further polymerization to the known polymeric trimethyltin hydroxide. Especially noteworthy is that the formate present in this structure was formed from atmospheric CO2.
Acta Cryst. E;72(10)
Keywords: Crystal structure; Tin; Trimethyltin hydroxide; Formate; Chloride; Hydrolysis; Hydrogen bonding; 540